The association between glycemic control and lung function impairment in individuals with diabetes: the Saku study - Sonoda, Nao (Diabetol Int, 2018)
AIM: Though diabetes is a risk factor for lung function impairment, whether the glycemic control level affects lung function in individuals with diabetes remains unclear. The present study aimed to assess the association between glycemic control level and restrictive or obstructive lung function impairment in individuals with diabetes. METHODS: This cross-sectional study included 1028 individuals with diabetes, aged 40–69 years, who underwent a medical checkup between April 2008 and March 2014. Hemoglobin A1c (HbA1c) was categorized as  < 6.9%, 7.0–7.9%, and  ≥ 8.0%. Restrictive and obstructive lung function impairment was defined by a forced vital capacity (FVC) < 80% predicted and a forced expiratory volume in 1 s to FVC ratio < 0.70. RESULTS: Of the participants, 8.7% and 6.3% were classified as having restrictive and obstructive lung function impairment, respectively. The multivariable-adjusted odds ratios and 95% confidence intervals for restrictive lung function impairment were 1.43 (0.84–2.42) in individuals with HbA1c 7.0–7.9%, and 2.42 (1.38–4.26) in individuals with HbA1c ≥ 8.0%, compared with those who had HbA1c < 6.9% (p for trend = 0.002). In contrast, glycemic control level was not associated with obstructive lung function impairment (p for trend = 0.749). CONCLUSIONS: Poor glycemic control was associated with restrictive lung function impairment in individuals with diabetes. Good glycemic control would be important to minimize restrictive lung function impairment in individuals with diabetes. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s13340-018-0382-y) contains supplementary material, which is available to authorized users.